MODERASI ISLAM: Untuk Peradaban dan Kemanusiaan - Sudarji Sudarji (Edukasia, 2020)
Abstract: Islam is inseparable from al-Qur'an and al-Hadith as a source of legal resources. But on the other hand, Islam is stigmatized as an extreme religion, in the name of religion originating from the Qur'an and as-Sunnah. This study aims to describe and track the moderation of Islam for civilization and humanity. This research includes qualitative research in the form of library research, which is descriptive through logical analysis. While the technique used in raising the data is by way of research or library research. study that Islam is a religion that wasathan. Moderate Islam that is reflected in the social organization of diversity in Indonesia has made a valuable contribution to the survival of the national level in particular and the world at large. Evidenced by the dialogue between organizations and religious social cooperation able to become a prototype in the public as a community of Muslims who provide fresh air for a harmonious and peaceful survival in reaching a civilized nation under the auspices of an earthly normative concept.